TRIBOLOGICAL PROPERTIES OF THERMAL SPRAY COATINGS - Geaman, Virgil; Pop, Mihai Alin; Motoc, Dana Luca; Radomir, Irinel (European Scientific Journal, ESJ, 2014)
Thermal spraying techniques are coating processes in which melted or heated materials are sprayed onto a surface. Thermal spray coatings have a wide range of applications, for instance, by repairing machine parts damaged in service or by the production of parts with high wear resistance. Coating quality is usually assessed by measuring its porosity, oxide content, macro and microhardness, bond strength and surface roughness. Generally, the coating quality increases with increasing particle velocities. The present paper analyses the thermal spray coatings by their tribological properties.